Need for a New Paradigm of Economic Development - Chobanova, Rossitsa (Research Papers, 2020)
A new stage in the economic development has been highlighted, associated with digitalization as a penetration of information and communication technologies in the economy and society. The new stage requires a new paradigm of development to be defined. Arguments are given based on the application of Hegel’s understanding of the development of society. Among them are contemporary inability of the subjects and means of development from the old stage to contribute to achievement the goals of the new stage of development; reduction of potential for development because of the very low intensity of research in the last 30 years; the inability to increase it from 0.5% to 1.5% for the country and to 3% for the EU; reduction of the demand for nationally based results in terms of global supply; accelerated lagging technological development of the country due to the very limited research and development resources.